Analysis of the Role of Parents Role in Home Numeracy - Gina Anggraini; Dindin Abdul Muiz Lidinillah; Ika Fitri Apriani (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2023)
The purpose of this study is to find out how the activities and roles of parents towards numeracy learning at home are reviewed based on parents with different types of jobs. The research method used is descriptive qualitative research. Data was collected using a questionnaire guideline which includes counting activities at home done with the mother, interview guidelines as clarifying material from the questionnaire which contains counting activities done with the mother and the media used. The results showed the role of (1) parents who work as entrepreneurs have played a good and compact role in providing facilities that support counting activities at home, (2) parents who work as self-employed are quite good at providing facilities for counting activities at home, this is because parents are less compact and less involved in the process of children learning to count at home, (3) while parents who work as teachers have played a very good role in providing facilities for counting activities at home, and always provide motivation. This shows that parents' awareness is an important point in teaching counting at home.